MASS AND STUDENT SPORTS IN UNIVERSITIES: PROBLEMS AND PROSPECTS - Babanov S. J. (Proximus Journal Publishing, 2025)
This article discusses the main ways to maintain a healthy lifestyle of young people of student age, problems and prospects for the development of mass student sports. The topic of students' interest in mass sports, ways of motivation is also considered. The requirements of physical training from a student at the initial stages of training are analyzed.
Keywords: Mass student sports; health